Hubungan Orientasi Interpersonal Dengan Partisipasi Mahasiswa Dalam Aktivisme Protokol Kesehatan Covid-19 Di Instagram - Alicia Laurence Efendi; Benazir Bona Pratamawaty (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
This study aims to examine the relationship between interpersonal orientation and student participation in COVID-19 health protocol activism on Instagram using the Individual Differences theory. This theory talks about how each individual has a different response to a message depending on his psychological setting. The population in this study were students in Indonesia with a sample size of 287 based on the calculation of the G*Power software. Data collection done online via Google Forms and will be processed using two-tailed Pearson Correlation via SPSS 25 software.  Keywords: interpersonal orientation; digital activism; health activism; student digital activism; Covid-19 health protocol